Examining the Mathematical Competences of Visually Challenged Students in the University of Bamenda- UBa, Cameroon - Nkepah, Beyoh Dieudone; Mboshi, Nsagha Sarah (American Journal of Education and Practice, 2024)
Purpose: The main purpose of this study was to explore the mathematical competencies and challenges faced by visually impaired students at the University of Bamenda, Cameroon. Inclusive education aims to provide equal opportunities for all students, yet visually challenged individuals encounter unique obstacles, particularly in subjects like mathematics heavily reliant on visual aids. Materials and Methods: This study investigates the proficiency of visually impaired students in mathematical, with delimitation in statistical concepts, aiming to assess the effectiveness of current teaching methods and identify areas for improvement. Employing a mixed-methods approach, data was collected from 13 visually impaired students using interviews and a validated questionnaire. Findings: Findings indicate that while students demonstrate proficiency in basic mathematical operations, they struggle with advanced concepts, particularly in statistics. Challenges include interpreting graphical data, accessing suitable materials, and comprehending statistical notation. Implications to Theory, Practice and Policy: Recommendations include developing accessible educational materials, implementing assistive technologies, and providing training for educators to enhance inclusive teaching practices. By addressing these challenges, educational institutions can foster a more inclusive learning environment for visually impaired students in mathematics and particularly, in statistics.